"THE METHODOLOGICAL FOUNDATIONS FOR ELIMINATING ETHICAL DESFORMATIONS IN PEDAGOGICAL COMMUNICATION" (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the methodological foundations for preventing ethical deviations in pedagogical communication by grounding the discussion within the framework of national values and contemporary pedagogical ethics. The study outlines key types of communicative distortions, including verbal aggression, disregard for student dignity, and misuse of authority. Drawing on educational psychology, communication theory, and didactic ethics, the paper proposes a value-based approach to shaping a respectful and morally sustainable pedagogical environment. Preventive strategies such as ethical modeling, dialogic pedagogy, reflexive practices, and culturally rooted communication standards are critically examined. The article concludes by emphasizing the necessity of integrating national cultural codes into teacher training to foster ethically grounded communication.